Nanostructure physics and fabrication : proceedings of the international symposium, College Station, Texas, March 13-15, 1989 - Reed, Mark A.; Kirk, Wiley P. (Academic Press, 1989)
Nanostructure Physics and Fabrication contains the contributions of an interdisciplinary group of specialists in nanometer scale fabrication, physics of mesoscopic systems, electronic transport, and materials science brought together to discuss the current status of nanometer scale electronic structures. These articles provide the most current assessment of this active and growing area of interest. The introductory chapter provides comments and background material for those somewhat unfamiliar with this new area of research and serves as a condensed overview and summary of the contributions that follow. Key Features * Most current assessment of the field * Articles by experts in the field * Results presented here will impact the future of microelectronics.